2022
DOI: 10.1021/acsami.2c07492
|View full text |Cite
|
Sign up to set email alerts
|

3D Culture Modeling of Metastatic Breast Cancer Cells in Additive Manufactured Scaffolds

Abstract: Cancer biology research is increasingly moving toward innovative in vitro 3D culture models, as conventional and current 2D cell cultures fail to resemble in vivo cancer biology. In the current study, porous 3D scaffolds, designed with two different porosities along with 2D tissue culture polystyrene (TCP) plates were used with a model breast cancer human cell line. The 3D engineered system was evaluated for the optimal seeding method (dynamic versus static), adhesion, and proliferation rate of MDA-MB-231 brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…These models [37] have achieved significant breakthroughs in mimicking the tumor microenvironment, understanding the regulation of tumor dormancy by the tumor microenvironment, and exploring the interactions between tumor cells and the microenvironment [38]. In addition, when immunotherapy is of great interest [39], co-culture systems containing other cells, such as immune cells designed using 3D models, may help us improve our success rate regarding drug screening and validation [40]. Therefore, in the future, research will still focus on several cancer tissues, as mentioned above, and studies on tumor dormant tumor microenvironments will remain prevalent [41].…”
Section: Discussionmentioning
confidence: 99%
“…These models [37] have achieved significant breakthroughs in mimicking the tumor microenvironment, understanding the regulation of tumor dormancy by the tumor microenvironment, and exploring the interactions between tumor cells and the microenvironment [38]. In addition, when immunotherapy is of great interest [39], co-culture systems containing other cells, such as immune cells designed using 3D models, may help us improve our success rate regarding drug screening and validation [40]. Therefore, in the future, research will still focus on several cancer tissues, as mentioned above, and studies on tumor dormant tumor microenvironments will remain prevalent [41].…”
Section: Discussionmentioning
confidence: 99%
“…STC1 was found to be a biomarker in many diseases [52][53][54][55] . In this study, we found that STC1 was highly expressed in HCC and was closely correlated with poor prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This scaffold not only promotes cell growth but also provides essential cues from the natural biophysics and biochemical environment, which are crucial for regulating tumor cell functions. 84 Currently, scaffolds for in vitro cancer modeling have evolved from natural hydrogels (such as proteins, polysaccharides), synthetic hydrogels (such as polyethylene glycol, peptides), and hybrid materials (with high water content, tissue-like bioresponsiveness, viscoelasticity, and mechanical properties). Advances in microfabrication techniques in recent years have enabled more complex and precise hydrogel platforms, which can replicate the fundamental characteristics of the tumor microenvironment (TME).…”
Section: Overview Of Tumor Model Constructionmentioning
confidence: 99%